STUDI PERBANDINGAN EMPAT PEGIAT KHILÂFAH ISLÂMIYYAH: TINJAUAN ATAS PENAFSIRAN KATA KHILAFAH DALAM AL-QUR’AN. - Rasyid, Muhammad Makmun (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2023)
This study shows that textual and methodological work is a necessity. Both are necessary in keeping God's message in the Qur'an. From the analysis and research of the literature obtained, four figures such as Rasyîd Ridhâ, Abû al-A'lâ al-Maudûdî, Sayyid Qutb and Taqiyuddîn al-Nabhânî only place the arguments for the caliphate or imâmah in the qauli (textual, literalism) area and nullify the work of manhaji (methodological). The principles of religion and state that the I get from this research are qath'i al-Dilalah zhanni al-Tathbîq. In the course of revelation, it is stated that in the context of tasyri', the Prophet waited for the revelation to come. But in the context of application, the Prophet involved the wider community by adjusting the socio-political reality. In short, even sharia texts that are qath'i in nature can sometimes be relative if they are to be applied. From several studies that reviewed the interpretation, including Qs. al-Baqarah [2]: 30 and 124, Qs. al-Nisâ [4]: 59, Qs. al-Mâ'idah [5]: 48-49, Qs. al-An'âm [6]: 165 and Qs. Yûnus [10]: 14. The four mufasir in carrying out the khilafah or imâmah system only consider the aqwâl of the scholars who can support legitimacy in their respective movements, but miss in reformulating social reality in the face of maqâshid al-Syâriah (the principle values/purposes of the islamic law) and maslahah 'ammah (public interest).